Evaluation of metaphors (life and self) of obese and overweight individuals in comparison with normal weight’s - Alimoradi, Mohammad; Abdollahi, Morteza; Vazirijavid, Roya; Mckian, Somayeh Sadat; Daneshvar, Somayeh; Ajami, Marjan (Progress in Nutrition, 2019)
Introduction: Obesity and overweight have become an epidemic & health’s public problem. Studies on obese individuals have shown associations between harms and disadvantages of obesity on physical and mental health as well as interpersonal relations. Metaphors in personal & social life make images of health-related issues. Methods: Study samples were selected from adults who referred to nutrition and diet therapy clinics in Tehran and baseline data were collected. After completing the questionnaires, quality control was re-examined. Results: In assessing the metaphors, the participants’ metaphors of life and self were analyzed by statistical calculations. On this basis, women with obesity have more negative “self metaphor” than the ordinary population and these women have more negative “life metaphor” than the ordinary population. Checking the content of incomplete sentences of life metaphors and self metaphors in all subjects confirm the fact that most codes with more negative metaphorical content have more repeat in obese subjects than normal weight subjects that psychological condition is very different in obese people. Conclusions: In all groups, there is a direct relationship between their attitude to life and to themselves (self) and overweight and obesity, and the more negative their attitude is, weight control is more difficult.